PENCEGAHAN DAN UPAYA MENGATASI PERILAKU PERUNDUNGAN PADA REMAJA - Sinaga, Andre Dwi Putra; Andino Carlos Sinaga; Bartolomeus Marulitua Simanjorang; Putri Lopiga Br.Tarigan; Maulana Ibrahim; Reh Bungana Beru Perangin-angin (International Forum of Researchers and Lecturers, 2023)
Bullying is an act that is not commendable and can cause enormous harm. Bullying is an aggressive behavior carried out by someone who is stronger to someone else who is weaker by committing acts of violence, humiliation, intimidation, exclusion, and even slander, which causes the victim to experience physical and psychological disorders. Bullying behavior can be caused by family, peers, social media, and environmental factors. Lack of parental and teacher supervision in educating children, setting bad examples for children at home, following peers to bully, following trends, following inappropriate behaviors in social media, and following bullying behaviors that occur in the surrounding environment are things that can cause bullying behavior to occur in children. Advise the perpetrator properly and make the perpetrator not repeat this again and immediately apologize to the victim. Provide more in-depth education to the perpetrator so that there is a change in behavior in the future and if he does it again, he will impose strict sanctions on the perpetrator so that he will be reported to the police.